Cerebellar ependymal cyst: a case report - Hou, Chengye; Liu, Yuanqin; Li, Feng; Zhang, Qinglu (Frontiers in Neuroscience, 2024)
Rationale Intracranial ependymal cysts are relatively rare. The current case report focuses on a patient who was diagnosed with an ependymal cyst and underwent surgical treatment. Postoperative pathological examination confirmed the presence of this lesion in the cerebellum. Chief complaint A 32-year-old female patient presented with a chief complaint of dizziness and headache with no triggers for the past 1 year. She also reported an increase in the frequency and intensity of symptoms in the past 2 weeks. Diagnosis Cranial magnetic resonance imaging (MRI) showed a rounded long T1 and T2 abnormal signal foci in the left posterior part of the brainstem under the cerebellar pallidum. The lesion had a clear boundary, was approximately 4.0 × 3.1 × 3.2 cm in size, and did not exhibit any definitive enhancement. Interventions Total resection of the lesion was carried out after completion of the preoperative examination. Treatment outcomes. The patient was discharged from the hospital on postoperative day 11 once their symptoms had disappeared. The sensory and motor functions of the limbs remained unaffected by treatment. Experiences Cerebellum ependymal cysts are rare, and most patients only experience discomfort due to cerebral edema. These lesions are also often difficult to differentiate from other intracranial cysts using imaging alone. The aim of this study was to report a rare case of ependymal cyst so that it may serve as a reference for diagnosis and treatment in the future.